2018
DOI: 10.1103/physrevlett.120.057002
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional Superconductivity in Luttinger Semimetals: Theory of Complex Tensor Order and the Emergence of the Uniaxial Nematic State

Abstract: We investigate unconventional superconductivity in three-dimensional electronic systems with the chemical potential close to a quadratic band touching point in the band dispersion. Short-range interactions can lead to d-wave superconductivity, described by a complex tensor order parameter. We elucidate the general structure of the corresponding Ginzburg-Landau free energy and apply these concepts to the case of an isotropic band touching point. For a vanishing chemical potential, the ground state of the system… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
105
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(106 citation statements)
references
References 52 publications
1
105
0
Order By: Relevance
“…This was recognized in important papers focusing on a specific set of fully gapped pairing states [25,26] and on-site pairings [27]. Reference [27], in particular, has set the stage for studying superconductivity in the half-Heusler compounds [28][29][30][31][32][33][34]; the present authors have investigated the pairing instabilities in the p-wave pairing channels [31].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…This was recognized in important papers focusing on a specific set of fully gapped pairing states [25,26] and on-site pairings [27]. Reference [27], in particular, has set the stage for studying superconductivity in the half-Heusler compounds [28][29][30][31][32][33][34]; the present authors have investigated the pairing instabilities in the p-wave pairing channels [31].…”
Section: Introductionmentioning
confidence: 91%
“…That such a degeneracy lifting should occur is expected from the gap structures of these states, as we demonstrate in the next section. Within weak-coupling BCS theory, it was found that the uniaxial nematic pairing is favored below T c [32].…”
Section: A Symmetry Properties and Stationary Pairing Statesmentioning
confidence: 99%
“…In addition, Weyl SM (WSM), in which the low-energy fermionic excitations display linear dispersion around pairs of nodes with opposite chirality, was observed in TaAs, NbAs, TaP, and NbP by the angle-resolved photoemission spectroscopy (ARPES) [10][11][12][13][14]. There also exist other types of SMs, such as 3D nodal line SM (NLSM) [15][16][17][18], 2D semi-DSM , 3D double-WSM [47][48][49][50][51][52][53][54][55][56][57][58][59], 3D triple-WSM [49,53,[56][57][58][59][60][61][62], 3D anisotropic-WSM [49,[63][64][65], and 3D Luttinger SM [66][67][68][69][70].…”
Section: Introductionmentioning
confidence: 99%
“…The difference is owing to the fact that the fermion DOS vanishes at zero energy, namely ρ(0)=0. Cooper pairing instability may be achieved in other SMs, including 2D semi-DSM [43,44], 3D DSM [96], 3D WSM [97,98], 3D NLSM [17,18], and 3D Luttinger SM [67,69,70]. In these materials, there is also a threshold value for the strength of attraction.…”
Section: Introductionmentioning
confidence: 99%
“…Crucially for the appearance of BFSs, internally anisotropic pairing states are typically characterized by both intraband and interband pairing potentials [3]. Such pairing states have been proposed for a wide variety of multiband systems of current interest, such as iron-based superconductors [9][10][11][12][13][14], Cu x Bi 2 Se 3 [15], half-Heusler compounds [2,3,[16][17][18][19][20][21][22][23], the antiperovskite Sr 3−x SnO [24], Sr 2 RuO 4 [25], UPt 3 [26,27], * henri.menke@gmail.com † carsten.timm@tu-dresden.de ‡ philip.brydon@otago.ac.nz transition metal dichalcogenides [28,29], and twisted bilayer graphene [30][31][32]. This long list of materials-some of which are believed to support a time-reversal-symmetrybreaking (TRSB) state-is encouraging for the existence of BFSs.…”
Section: Introductionmentioning
confidence: 99%